Implementation of thyroid-related patient-reported outcomes in routine clinical practice - Cramon, Per Karkov; Bjorner, Jakob Bue; Groenvold, Mogens; Boesen, Victor Brun; Bonnema, Steen Joop; Hegedüs, Laszlo; Feldt-Rasmussen, Ulla; Rasmussen, Åse Krogh; Watt, Torquil (Frontiers in Endocrinology, 2022)
Patient-reported outcomes (PROs) are increasingly used in clinical practice to improve clinical care. Multiple studies show that systematic use of PROs can enhance communication with patients and improve patient satisfaction, symptom management and quality of life. Further, such data can be aggregated to examine health levels for patient groups, improve quality of care, and compare patient outcomes at the institutional, regional or national level. However, there are barriers and challenges that should be handled appropriately to achieve successful implementation of PROs in routine clinical practice. This paper briefly overviews thyroid-related PROs, describes unsolved quality of life issues in benign thyroid diseases, provides examples of routine collection of PROs, and summarizes key points facilitating successful implementation of thyroid-related PROs in routine clinical practice. Finally, the paper touches upon future directions of PRO research.